Implementasi One-Time Password (OTP) Dengan Algoritma SHA-512 Untuk Peningkatan Keamanan Login Pada Aplikasi Absensi Siswa MAN 1 Bekasi - Amali; Randi Saepudin Kusmayadi (Prosiding Sains dan Teknologi, 2025)
There are more and more information systems for school needs, including attendance systems. The attendance system is important in the ongoing teaching and learning activities in schools, especially for students. Security is very important for someone, everyone needs security and comfort in their life. Thus developments in the field of technology are designed to provide security and protect one's assets. In addition to this, of course, the application of a security system that will be designed can reduce the number of fraud that occurs in students, especially absenteeism fraud. The login process is part of the system that authenticates users. The login process still uses the same password every time it logs into a system. This is still not safe enough to protect users from irresponsible parties. Therefore, to minimize the use of the system by unauthorized persons, it is necessary to use the One-Time Password method in a login system. One-Time Password is a password that is only valid for a single login session or single transaction. It is hoped that the designed student attendance system will help shorten time, make it easier for teachers to recapitulate attendance data. Researchers used the Agile Software Development method in designing the proposed system. This research was conducted using the Secure Hash Algorithm method to implement One-Time Password (OTP). OTP can be a fairly appropriate solution for securing data in a student attendance system. One of the cryptographic methods, namely the hash function is used to be able to create an OTP password and the character selection is chosen randomly with the Pseudo Random Number Generator.